Lianglad Kati Lukhe Tasii Phibang Pachen IX - X - (:unkn) unknown (Liangmai Text Book Producing Committee Manipur, 2014)
The book is prescribed as MIL textbook for class IX and X by Board of Secondary, Manipur. The book consist of Liangmai Grammar and composition.
Keywords: Liangmei; Lianglad Kati Lukhe Tasii Phibang Pachen IX - X; Grammar & Composition; Liangmei